Assessment of Gingival Health Status among 5- and 12-Year-Old Children in Yemen: A Cross-Sectional Study. (26th June 2013) - Al-Haddad, Khaled A.; Ibrahim, Yahia T.; Al-Haddad, Ahmed M.; Al-Hebshi, Nezar N.
Abstract : Purpose . There are limited data about the gingival health status in Yemeni children. The aim, therefore, was to assess oral hygiene status and prevalence and severity of gingivitis among Yemeni preschool and school children. Materials and Methods . A total of 5396 children were included from 5 representative Yemeni governorates: Sana'a, Hajjah, Hodeida, Hadramaut, and Taiz. Five-year olds (1292) were recruited from private kindergartens while 12-year olds (4104) were selected from public primary schools. Gingival health status was assessed using the plaque index (PI), calculus index (CAI), and gingival index (GI) on the 6 Ramfjord teeth. The latter index was used to categorize gingivitis severity at the subject level. Data were analyzed using simple hypothesis testing, as well as ordinal regression. Results . The 12-year old children had significantly much higher mean PI, CAI, and GI (P < 0.001 ) with 78.6% presenting with gingivitis and 47.8% with moderate gingivitis. In contrast, the figures were 27.2% and 3.1% in the younger group (P < 0.001 ). There were significant variations according to gender, area of residence, and governorate. Regression analysis revealed that mean PI (OR = 35 ), mean CAI (OR = 7.7 ), male gender (OR = 1.6 ), living in rural areas (OR = 1.4 ), and being from Hajjah or Sana'a were independent risk factors of gingivitis severity in the older group. For the 5-year olds, the determinants were mean PI (OR = 122 ), male gender (OR = 1.4 ), and living in Sana'a or Taiz. Conclusions . Bad oral hygiene and moderate gingivitis are highly prevalent among Yemeni preschool and school children. Geographical location appeared as important independent risk factors of gingival inflammation.